2018
DOI: 10.1155/2018/7109061
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of CFRP‐Confined CFST Stub Columns under Axial Compression

Abstract: is paper presented a comparative study of concrete-filled steel tubular (CFST) stub columns with three different confinement types from carbon fiber reinforced polymer (CFRP): outer circular CFRP, inner circular CFRP, and outer square CFRP. e compressive mechanism and physical properties of the composite column were analyzed firstly aiming at investigating the confinement effect of CFRP. Ultimate axial bearing capacity of these three CFRP-confined CFST columns was calculated based on Unified eory of CFSTand el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…e eight-node reduced integration linear solid elements with three translation degrees of freedom (C3D8R) were utilised for modelling the steel tube, corrugated steel plate, concrete and loading plates [1][2][3][4]. Obviously, the thin-walled steel tube used in the ISSCC column buckles locally outwards with the extrusion provided by the filled concrete.…”
Section: Element Type and Sizementioning
confidence: 99%
See 2 more Smart Citations
“…e eight-node reduced integration linear solid elements with three translation degrees of freedom (C3D8R) were utilised for modelling the steel tube, corrugated steel plate, concrete and loading plates [1][2][3][4]. Obviously, the thin-walled steel tube used in the ISSCC column buckles locally outwards with the extrusion provided by the filled concrete.…”
Section: Element Type and Sizementioning
confidence: 99%
“…e damageplasticity model was used in the FE model to simulate the concrete, and the value of dilation Angle (ψ) was 35°, which was determined by using equation (1). e flow potential eccentricity was taken as the default value of 0.1.…”
Section: Materials Constitutive Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the components, Zhou et al [5], Kim et al [6], and Han et al [7] conducted pseudostatic tests on intersecting nodes in the diagrid structure and analysed the force mechanism and hysteresis performance under axial cyclic loads; however, the relevant research on inclined CFST columns in diagrid structures is still in the initial stage. Currently, the studies on CFST columns mainly focus on the monotonic behaviour of vertical bearing members and the seismic performance of lateral force-resistance components [8][9][10][11][12][13][14][15], while minimal research has focused the mechanical behaviour under cyclic loads of components such as lateral braces [16,17], and few studies have been conducted on the mechanical behaviour of the inclined CFST columns under cyclic axial loads, which are the major components of the diagrid structure.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement in materials, the effect of high material strength was investigated by Liu et al [6] and Zhou et al [7]. Using of carbon fiber reinforced polymer (CFRP) to confine the CFST columns was investigated by Guo and Zhang [8]. e study indicated the increase of confinement using the outer CFRP especially for the square column.…”
Section: Introductionmentioning
confidence: 99%